2020
DOI: 10.1016/j.ajog.2020.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Screening all pregnant women admitted to labor and delivery for the virus responsible for coronavirus disease 2019

Abstract: This communication has been published in the middle of the coronavirus disease 2019 pandemic and is available via expedited publication to assist patients and healthcare providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
139
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(157 citation statements)
references
References 2 publications
7
139
2
5
Order By: Relevance
“…Outpatient antibiotic misuse is widespread in the United States and has been associated with several patient harms, including Clostridioides difficile infections, adverse drug reactions, and rising rates of antibiotic resistance. 1,2 Recent estimates suggest that~30% of the >200 million outpatient antibiotic prescriptions in the United States each year may be inappropriate. [3][4][5] Although outpatient antibiotic misuse is common, it remains difficult to identify and study.…”
Section: Division Of Infectious Diseases Icahn School Of Medicine Atmentioning
confidence: 99%
See 1 more Smart Citation
“…Outpatient antibiotic misuse is widespread in the United States and has been associated with several patient harms, including Clostridioides difficile infections, adverse drug reactions, and rising rates of antibiotic resistance. 1,2 Recent estimates suggest that~30% of the >200 million outpatient antibiotic prescriptions in the United States each year may be inappropriate. [3][4][5] Although outpatient antibiotic misuse is common, it remains difficult to identify and study.…”
Section: Division Of Infectious Diseases Icahn School Of Medicine Atmentioning
confidence: 99%
“…They found that 14% of asymptomatic women tested positive. 1,2 Unidentified, these asymptomatic women were at risk of infecting their newborns following birth, hospital staff, as well as other patients. It is unclear, however, whether the high rate of asymptomatic infections in New York is a reflection of a particularly high prevalence of SARS-CoV-2 during that time period in New York or a more generalizable phenomenon applicable to other high-prevalence areas.…”
mentioning
confidence: 99%
“…The variation of the monitored laboratory parameters is shown in Table 2. positive for SARS-CoV-2, as well as for pregnant women suspected to be infected (those with travel history, contacts of SARS -Cov-2 positive persons or presenting respiratory symptoms) [2], [3], [10], [11].…”
Section: Laboratory Datamentioning
confidence: 99%
“…The risk of contamination of the newborn seems higher in the immediate postnatal period, from the infected symptomatic or healthy carrier mother, if strict hygienic measures are not respected during skin-to-skin care. Due to COVID − 19 high contagion, obstetricians, neonatologists and infectionists have focused on the implementation of preventive measures in all areas (from the delivery room, to the neonatal, maternity ward and intensive care unit) to limit the risk of viral transmission [3], [7]- [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation